Tetrapod association and palaeoenvironment of the Los Colorados Formation (Argentina): A significant sample from Western Gondwana at the end of the Triassic - Arcucci, Andrea Beatriz (2004)
The Los Colorados Formation constitutes a continuous continental succession deposited in Western Argentina during the Late Triassic, a time period that is crucial to the record of the faunistic turnover at the Triassic-Jurassic boundary. Many authors have pointed out that its rich tetrapod fauna represents a unique transitional assemblage with elements typical of both Late Triassic and Early Jurassic. However, the possibility that the fauna represented a mixture of Triassic and Jurassic horizons was also proposed. Recently, stratigraphic control of the fossiliferous levels was developed in order to correlate the different localities of the extense Los Colorados outcrops, and a revision of the taxonomic status of most tetrapods recovered is currently undergoing. Preliminary results confirm previous assumptions about the transitional nature of the assemblage where typical Triassic taxa are associated with dinosaur groups known from Early Jurassic levels in other Gondwanan areas. The fossiliferous levels of the upper third of the sequence included several basal archosaurs (aetosaurs, rauisuchids, sphenosuchians), protosuchian crocodiles, dinosaurs (sauropodomorphs, tetanuran theropods), derived therapsids and primitive chelonians. New evidence about tetrapod ichnites of chirotheroid affinities is added to the fossiliferous association.